2021
DOI: 10.1186/s12877-021-02338-z
|View full text |Cite
|
Sign up to set email alerts
|

Digital health interventions for healthy ageing: a qualitative user evaluation and ethical assessment

Abstract: Background Digital health technologies are being increasingly developed with the aim of allowing older adults to maintain functional independence throughout the old age, a process known as healthy ageing. Such digital health technologies for healthy ageing are expected to mitigate the socio-economic effects of population ageing and improve the quality of life of older people. However, little is known regarding the views and needs of older people regarding these technologies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 23 publications
0
67
0
2
Order By: Relevance
“…From this perspective, Ienca et al (2021) [ 58 ] found that effective digital health technologies for healthy aging can be interpreted as an empowering factor that facilitates aging in place. These patient-centered technologies, created to promote freedom and independent living, are more likely to be adopted and appreciated by community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, Ienca et al (2021) [ 58 ] found that effective digital health technologies for healthy aging can be interpreted as an empowering factor that facilitates aging in place. These patient-centered technologies, created to promote freedom and independent living, are more likely to be adopted and appreciated by community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In the digitized world, surprisingly, little is known about the needs of older people regarding their use of digital technologies for healthy lifestyle promotion [3]. Although older people are considered "nondigital natives" and their use of digital technologies is associated with various barriers, such technologies could also facilitate healthy aging via access to health information and the provision of health care [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Digital health has provided a safe alternative to in-person visits for vulnerable and home-bound patients, reduced travel burden, and facilitated communication with providers [ 9–11 ]. For these reasons, older adults are increasingly viewing digital health as essential to their lives [ 12 , 13 ]; however, many healthcare professionals remain reluctant [ 14 , 15 ].…”
Section: Rapid Growth Of Digital Healthmentioning
confidence: 99%